Temperature-dependent breakdown of hydrogen peroxide-treated ZnO and TiO2 nanoparticle agglomerates - Sabuncu, Sinan; Çulha, Mustafa (Beilstein Journal of Nanotechnology, 2015)
Metal oxide nanoparticles (MONPs) are used in a variety of applications including drug formulations, paint, sensors and biomedical devices due to their unique physicochemical properties. One of the major problems with their widespread implementation is their uncontrolled agglomeration. One approach to reduce agglomeration is to alter their surface chemistry with a proper functionality in an environmentally friendly way. In this study, the influence of hydrogen peroxide (H2O2) treatment on the dispersion of ZnO and TiO2 nanoparticle (NP) agglomerates as a function of temperature is studied. The H2O2 treatment of the MONPs increases the density of hydroxyl (–OH) groups on the NP surface, as verified with FTIR spectroscopy. The influence of heating on the dispersion of H2O2-treated ZnO and TiO2 NPs is investigated using dynamic light scattering. The untreated and H2O2-treated ZnO and TiO2 NP suspensions were heated from 30 °C to 90 °C at 5 °C intervals to monitor the breakdown of large aggregates into smaller aggregates and individual nanoparticles. It was shown that the combined effect of hydroxylation and heating enhances the dispersion of ZnO and TiO2 NPs in water.
Keywords: agglomeration; hydrogen peroxide; metal oxide nanoparticles; TiO2; ZnO